The Practice of Muhallil Marriage as a Legal Loophole in The Enforcement of Islamic Family Law in Indonesia - Kusuma Putri, Kristiani Virgi; Jannah, Hilda Rahmatul; Wulandari, Niken Retno; Maulana, Moch. Ahsin; Setiawan, Regina Farah (Fakultas Syariah UIN Antasari, 2025)
Marital conflicts may lead to divorce, and after a third talaq, reconciliation is only lawful through nikah muhallil. Although valid if meeting legal requirements, the Prophet Muhammad (PBUH) condemned this practice when done merely to allow remarriage with a former husband, as it opposes the true purpose of marriage. This normative juridical study analyzes Indonesian Islamic family law enforcement concerning nikah muhallil using statutory and ushul fiqh approaches. Findings reveal that while Al-Baqarah 2:230 is often cited to justify nikah muhallil, its misuse legitimizes contractual marriages that undermine women’s dignity and the noble aims of marriage (maqashid al-nikah). Currently, Indonesian law does not explicitly regulate this practice. Existing laws—such as the Marriage Law and the Compilation of Islamic Law (KHI)—stress marriage’s goal of building a lasting, harmonious family. However, due to legal gaps, nikah muhallil still occurs in areas like Padarincang, Kampar, and Muko Muko Bathin VII. Therefore, reformulating the KHI to explicitly prohibit nikah muhallil and strengthening premarital education are essential to preserve the sanctity and justice of marriage.